DAMPAK PENJAJAHAN TERHADAP PERKEMBANGAN BAHASA - Perawati Perawati; Adinda Maulidia Zahra; Widia Agita Barus (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study examines the impact of Dutch colonialism on the development of language in Indonesia, focusing on its role in shaping national identity through language. The colonial period introduced Dutch language in various aspects of life, such as education and governance, which ultimately led to an awareness of the importance of local language as a tool for resistance and unity. The 1928 Youth Congress marked the beginning of Indonesian language recognition as a unifying language. This study uses a literature review method to understand the colonial influence on language evolution and language policy in Indonesia, establishing it as a symbol of national identity.